2015
DOI: 10.1590/1807-3107bor-2015.vol29.0024
|View full text |Cite
|
Sign up to set email alerts
|

Sleep bruxism and anxiety level in children

Abstract: This study evaluated the association of level of anxiety in children with and without sleep bruxism (SB). The study was performed with 84 six-to eigth-years-old children, divided into two groups: with bruxism (BG) and without bruxism (CG). Following the criteria purposed by American Academy of Sleep Medicine (AASM) to determine SB, the presence of tooth wear has been verified through clinical examinations, and the parents have answered a questionnaire about their children's behavior and habits. Additionally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 8 publications
(13 reference statements)
2
36
0
19
Order By: Relevance
“…In a novel experiment, Babson et al () assessed the relationship between self‐reported sleep disturbance and the subsequent physiological arousal induced by a three minute, voluntary hyperventilation task in a community‐based sample of youths. Those who reported worse sleep quality reported significantly greater anxiety and intensity of panic symptoms following the hyperventilation challenge, even after controlling for age, gender and anxiety sensitivity.…”
Section: Child‐ and Parent‐report Of Sleep Disturbance And Anxiety Symentioning
confidence: 99%
See 1 more Smart Citation
“…In a novel experiment, Babson et al () assessed the relationship between self‐reported sleep disturbance and the subsequent physiological arousal induced by a three minute, voluntary hyperventilation task in a community‐based sample of youths. Those who reported worse sleep quality reported significantly greater anxiety and intensity of panic symptoms following the hyperventilation challenge, even after controlling for age, gender and anxiety sensitivity.…”
Section: Child‐ and Parent‐report Of Sleep Disturbance And Anxiety Symentioning
confidence: 99%
“…Sleep bruxism is the nocturnal grinding, rubbing and clenching of the teeth, and can be assessed by dental wear of the enamel, enamel and dentin, and/or crown. While bruxism is thought to correspond with most sleep disorders (de Oliveira et al ., ), the connection with anxiety is unclear. However, de Oliveira and colleagues () examined the relationship between sleep bruxism in children with anxiety as reported by their parents.…”
Section: Objective Measures Of Sleep and Anxiety Symptomsmentioning
confidence: 99%
“…Although none of the questions was assumed as right, the FTQ showed greater coherence with factors already recognized as associated with childhood bruxism, considering behavioral and sleep characteristics 5,8,10,[12][13][14][15] . The AASM recommends the evaluation of the occurrence of audible teeth grinding during the night as a criterion for the definition of PSB 1 , however it does not indicate any validated questionnaire for this purpose.…”
Section: Discussionmentioning
confidence: 92%
“…The current scientific evidence about bruxism in children present various aspects that are still inconclusive, however, they already indicate that SB is more prevalent in younger children, with worse sleep quality and with anxious 8,9 or nervous behaviors 6,10,11 . Although none of the questions was assumed as right, the FTQ showed greater coherence with factors already recognized as associated with childhood bruxism, considering behavioral and sleep characteristics 5,8,10,[12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira ve arkadaları, 84 çocuk hasta ile yaptıkları çalımada anksiyete seviyelerini değerlendirmi ve anksiyete seviyesini bruksizmi olan çocuklarda Arşiv Kaynak Tarama Dergisi . Archives Medical Review Journal olmayanlara oranla daha yüksek bulmutur 62 . SerraNegra ve arkadaları, 183 di hekimliği öğrencisi ile yaptıkları çalımada bruksizm ile uyku kalitesi arasında anlamlı bir iliki bulmutur.…”
Section: Etiyolojiunclassified